PERANCANGAN GAME EDUKASI INTERAKTIF BERBASIS WEB UNTUK PEMBELAJARAN SIRAH NABAWIYAH DENGAN SISTEM ADAPTIF MENGGUNAKAN FUZZY LOGIC: DESIGN OF A WEB-BASED INTERACTIVE EDUCATIONAL GAME FOR LEARNING SIRAH NABAWIYAH WITH AN ADAPTIVE SYSTEM USING FUZZY LOGIC - Mirza Mirza; Wahyu Fuadi; Rini Meiyanti (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
This study aims to develop a web-based interactive educational game designed specifically to help students understand the subject of Sirah Nabawiyah in a more engaging and adaptive way. In its development, the system adopts a fuzzy logic approach as an adaptive method that allows the adjustment of question difficulty levels based on each user’s ability. The system utilizes parameters such as score, response speed, and answer accuracy, which are processed to classify users into three ability categories: Advanced, Intermediate, or Beginner. The development process follows the waterfall methodology through the stages of needs analysis, system design, implementation, and testing. Black box testing results indicate that all features function properly and the system is capable of delivering accurate adaptive responses. Furthermore, trials conducted with 30 elementary school students showed a 28% improvement in material comprehension, based on a comparison between pre-test and post-test results before and after using the educational game. Thus, the implementation of fuzzy logic in this educational game provides a tangible contribution to technological innovation in Islamic education, particularly in delivering religious content in a digital and enjoyable manner for elementary students.